Sex-specific effects of music listening on couples’ stress in everyday life - Wuttke-Linnemann, Alexandra; Ditzen, Beate (Scientific reports, 2019)
Music listening in daily life is associated with stress-reducing effects on the individual with increasing effects when music listening occurs in a social context. As little is known about effects on couples, we investigated whether beneficial effects can be found in couples. Forty heterosexual couples were investigated using ambulatory assessment. Participants completed six assessments on music listening and subjective stress per day for five consecutive days. With each assessment, saliva samples for the later analysis of cortisol and alpha-amylase were collected. Music listening affected biopsychological stress markers in women and men, however in different ways: While music listening reduced cortisol in women, it increased alpha-amylase in men. Dyadic effects of music listening on stress markers were found. Men showed lower secretion of cortisol if women listened to music which was more pronounced when couples shared musical preferences. Both men and women showed higher alpha-amylase activity when their partner had listened to music. Music listening influences couples’ psychobiological stress levels in a sex-dependent manner with evidence of dyadic co-variation in physiological responses to music. Interventions for promoting stress reduction should consider that women and men differ in their use of music in everyday life.
Gesehen am 18.06.2019